La educación para la salud y la educación popular, una relación posible y necesaria. - Zea Bustamante, Luis Emilio (Revista Facultad Nacional de Salud Pública)
The health sector has become a favorable scenario for the development of educational actions in different areas and scenarios through the adoption of different elements and methodologies. The theoretical progress of education for health has shown the need for pedagogical reflections to redirect the actions both in the clinical and the community environments. This effort on pedagogically nurturing education for health allows looking at the field of education as a natural scenario for pedagogical reflection; popular education is then the right place to have an interdisciplinary dialogue between health and education. Thanks to the epistemological, pedagogical and political development of popular education, it can be the scenario of confluence and articulation where education in the health sector reconsiders certain reflections that allow it to further consolidate as a transformation scenario. Of the many aspects that popular education could provide to education for health, dialogue as the epicenter of educational actions and the bet on a critical subject are chosen, as they become central elements of any educational process that may originate in the health sector.